GENETIC DIVERSITY IN SPRING WHEAT GENOTYPES UNDER DROUGHT STRESS IN BANGLADESH (Bangladesh Journal of Plant Breeding and Genetics, 2013)
Thirty local and exotic wheat genotypes were evaluated in alpha lattice design with three replications at the Regional Wheat Research Centre (RWRC), Bangladesh Agricultural Research Institute (BARI), Rajshahi during Rabi season of 2010-11. The main objective of this study was to identify the extent of genetic diversity for traits related to drought tolerance mechanism. Genotypes were grouped into five different clusters. Cluster V comprised with the maximum number of genotypes (eleven) followed by cluster III with six and IV with five genotypes. Inter-cluster distance was maximum between clusters I and II (15.03) indicated wide genetic diversity between the genotypes of these two clusters followed by the distance between cluster I and III (14.20). The highest inter genotypic distance (1.5566) was estimated between the genotypes G4 and G18 and the lowest (0.2240) between G13 and G14. Among the characters, early ground coverage, initial plant m-2, days to heading, peduncle length and chlorophyll content of flag leaf at 14 days after anthesis contributed the maximum for divergence in the genotypes investigated. It revealed that these parameters contributed more to grain yield under drought stress. Cluster I had the highest grain yield ha-1, spikes m-2, TDM and LAI at 86 DAS, CTgf, peduncle length and plant height. Cluster II exibitted the lowest days to heading, days to maturity, plant height, CTgf , chlorophyll content at 14 days after anthesis, LAI, TDM and spikes m-2 . Crosses between I and II, I and III, I and IV, III and V and II and V have greater chance to generate more heterotic F1s. Considering magnitude of genetic distance, contribution of different traits towards total divergence, magnitude of cluster means for different traits and performance the genotypes; G30, G6 and G28 of cluster I, G18 and G7 of cluster II and G25, G27 , G19, G2 and G1 of cluster V could be utilized as parents for future hybridization programme to improve drought-tolerant high yielding wheat crop.DOI: http://dx.doi.org/10.3329/bjpbg.v26i1.19977